2003
DOI: 10.1007/s11745-003-1104-y
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of croton oil inflammation by topical emu oil in CD‐1 mice

Abstract: Emu oil is derived from the emu (Dromaius novaehollandiae), which originated in Australia, and has been reported to have anti-inflammatory properties. Inflammation was induced in anesthetized CD-1 mice by applying 50 microL of 2% croton oil to the inner surface of the left ear. After 2 h, the area was treated with 5 microL of emu, fish, flaxseed, olive, or liquified chicken fat, or left untreated. Animals were euthanized at 6 h postapplication of different oils, and earplugs (EP) and plasma samples were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 26 publications
2
68
0
Order By: Relevance
“…Found throughout the world, the oils derived from other ratites, especially emu oils (Dromaeus novaehollandiae) are the most valuable products in many branches of industry, cosmetics, and nutrition. Emu oils have been claimed to have anti-inflammatory properties (Snowden & Whitehouse, 1997;Yoganathan et al, 2003), which are associated with causing a decrease in the production of proinflammatory cytokines (Whitehouse & Butters, 2003). It has also been reported that emu oil possesses the antioxidant and radical scavenging properties (Bennett, Code, Godin, & Cheng, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Found throughout the world, the oils derived from other ratites, especially emu oils (Dromaeus novaehollandiae) are the most valuable products in many branches of industry, cosmetics, and nutrition. Emu oils have been claimed to have anti-inflammatory properties (Snowden & Whitehouse, 1997;Yoganathan et al, 2003), which are associated with causing a decrease in the production of proinflammatory cytokines (Whitehouse & Butters, 2003). It has also been reported that emu oil possesses the antioxidant and radical scavenging properties (Bennett, Code, Godin, & Cheng, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…EO is composed predominately of fatty acids, with a lipid content of 98.8% for the subcutaneous adipose tissue and 98% for the retroperitoneal adipose tissue. EO is a natural source of 18:1 (n-9) fatty acid (oleic acid), which constitutes ϳ43-46% of the fatty acid composition, with 18:3 (n-3) linolenic acid (9.6%), palmitic acid (23.5%), and 18:2 (n-6) linoleic acid (0.6%) (53). The remaining 1-2% is yet to be identified; however, natural antioxidants such as carotenoids and flavones are present in the EO (24).…”
mentioning
confidence: 99%
“…EO has been used as an anti-inflammatory agent by Australian aboriginals to treat arthritis and joint pains for hundreds of years (43). Recent studies have focused on the effects of EO on arthritis and dermal inflammation in animal models (47,53). Topical application of EO to animals has been shown to reduce the levels of TNF␣ and other proinflammatory cytokines in a model of adjuvant-induced inflammation (53).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Emu oil mainly consists of several types of fatty acids, carotenoids, flavones, polyphenols, tocopherol, and phospholipids (Brown et al 1995). Several studies have indicated that emu oil reduces the inflammatory response by suppressing the expression of pro-inflammatory cytokines, resulting in reduced oxidative injury and rapid wound healing and recovery (Politis and Dmytrowich 1998;Yoqanathan et al 2003;Bennett et al 2008). The anti-inflammatory effect of emu oil in canine skin infection requires further investigation.…”
Section: Discussionmentioning
confidence: 99%